Examination of the Tax Treatment of Cryptocurrency Transactions in Nigeria - Ahmed, Isau (ABUAD Law Journal, 2021)
Tax is assessed and paid in the legal tender in which the transaction was conducted. A legal tender is a fiat currency centrally issued by the government through its Central Bank and is legally declared and designated as money to meet all kinds financial obligations including payment of taxes and debts within the boundary of a particular country. However, advancements in technology led to the emergence of virtual medium of payment such as ‘cryptocurrency’ which do not enjoy legal tender status like fiat currency. Over the past decade, there has been an increased number of transactions in Nigeria where cryptocurrency was the means of payment. This raises the question as to how such transactions will be assessed to tax bearing in mind that tax can only be assessed and paid in the currency in which the transaction was conducted. In addition, the virtual nature of cryptocurrency creates opportunities for tax avoidance thereby constituting a serious tax challenge for a developing country such as Nigeria. It therefore becomes necessary to address the taxation of cryptocurrency transactions to prevent tax avoidance that can arise therefrom. This objective of this article is toexamine the nature and the legal status of cryptocurrency. The article will also examine the tax treatment of cryptocurrency in some selected tax jurisdictions as well as the tax challenges posed by cryptocurrency transactions.